ASSESSING THE EVIDENCE BASE FOR USING CONFLICT-SENSITIVE APPROACHES TO IMPROVE DEVELOPMENT OUTCOMES IMPACTING YOUTH AND CHILDREN: A SYSTEMATIC REVIEW OF THE RESEARCH - Campie, Patricia; Lichtenfels, Chandler Hill; Chaplin, Kirsten (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2025)
This article examines the evidence base for using conflict-sensitive approaches to improve development outcomes in human-serving sectors. The study employed a systematic review methodology to identify and analyze evidence from a corpus of 49 studies that met inclusion criteria from a universe of 571 papers. Results from this review indicate that the evidence base is underdeveloped for demonstrating outcomes from integrating conflict-sensitive practices within human-serving sectors. We find that the evidence gaps may be the result of inconsistencies among the definitions and methods of measurement for conflict-sensitive practice and subsequent evaluations of such practices. Evidence from our review suggests that the education sector has developed the largest number of concrete conflict-sensitive tools and practices that can be formally evaluated for impact on outcomes and brought to scale for the benefit of the sector and the broader development community.